Increased risk of skin cancers in mucous membrane pemphigoid: a large-scale matched cohort study of 117 million US individuals - Nouri, Amar; Olbrich, Henning; Schmidt, Enno; Ludwig, Ralf J.; Curman, Philip (Frontiers in Medicine, 2025)
IntroductionMucous membrane pemphigoid (MMP) is an autoimmune disease affecting the oral mucosa, conjunctivae and other mucous membranes. The mainstay treatment options are local and systemic corticosteroids and immunomodulatory therapies. Current research on cancer risk in MMP is scarce and has yielded conflicting results.MethodsThe aim of this study was to investigate the risk of developing skin cancer in patients with MMP by performing a large-scale, retrospective matched cohort study utilizing data from over 117 million US individuals. The risk of skin cancer in patients with MMP was observed within a 5-year follow-up period, along with three temporal difference analyses and stratification for disease severity.ResultsMMP was associated with an increased risk of several types of skin cancers within the first 5 years of follow-up, particularly squamous cell carcinoma, basal cell carcinoma, and non-melanoma skin cancer. Stratification by disease severity showed significantly elevated risks in severe cases.DiscussionThese findings underscore the importance of regular skin cancer screening and risk-based monitoring in MMP patients, particularly those with severe disease. Integrating dermatologic surveillance into routine care could facilitate early detection and timely intervention. Additionally, these results highlight the need for further research into cancer risks in other autoimmune blistering diseases, helping to refine long-term management strategies.